2021
DOI: 10.21315/mjms2021.28.1.10
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Nutritional Status, Knowledge and Type 2 Diabetes Risk Among Malaysian Young Adults With and Without Family History of Diabetes

Abstract: Background: Genetic factors increase the risk of type 2 diabetes mellitus (T2DM). Thus, family history status may be a useful public health tool for disease prevention. This study compared the nutritional status, knowledge level, and T2DM risk among young adults with and without a family history of diabetes in Malaysia. Methods: A total of 288 university students aged 18 to 29 years participated in this comparative cross-sectional study. We assessed dietary intake, level of physical activity, knowledge of dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Ser mujer agrega mayor riesgo para desarrollar DT2, así como la rama parental materna de transmisión. Promover el conocimiento de las enfermedades de los ancestros y el uso de la genealogía como herramienta para prevención y promoción de la salud es fundamental para frenar el incremento de casos en poblaciones susceptibles (45)(46)(47).…”
Section: Discussionunclassified
“…Ser mujer agrega mayor riesgo para desarrollar DT2, así como la rama parental materna de transmisión. Promover el conocimiento de las enfermedades de los ancestros y el uso de la genealogía como herramienta para prevención y promoción de la salud es fundamental para frenar el incremento de casos en poblaciones susceptibles (45)(46)(47).…”
Section: Discussionunclassified
“…Family history reflects both genetic and environmental factors and thus serves as an independent predictor of T2D risk (Harrison et al, 2003). A previous study in Malaysia suggested using a family history of diabetes as a simple and quick screening tool to identify individuals at high risk of T2D (Hasbullah et al, 2021). A study involving Japanese women with a family history of diabetes in their early 20s found a correlation between family history of diabetes and postprandial hyperinsulinemia (Takeuchi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes risk score tools have been developed to improve risk stratification, enhance early detection of T2D, identify individuals with undiagnosed diabetes, and raise awareness in the population to modify risk factors and practice a healthier lifestyle (Saleem et al, 2017;Dugee et al, 2015). Some of the diabetes risk score tools that have been used in the Malaysian population include the Australian T2D risk assessment tool (AUSDRISK) (Hasbullah et al, 2021), Finnish Diabetes Risk Score (FINDRISC) (Lim et al, 2020;Oo et al, 2020) and Indian Diabetes Risk Score (Abdullah et al, 2018). Nonetheless, none of these studies assessed T2D risk specifically in Malaysian women of childbearing age.…”
Section: Introductionmentioning
confidence: 99%
“…According to world population review, as of 2022, Malaysia is now ranked at number 16 in the world with 19.0% (6.3 million) of prevalence rate diagnosed with diabetes [6]. Diabetes is not only incurable, but it also increases the chance of various health problems and microvascular compilations such as heart disease, nerve damages (neuropathy), strokes, hearing loss, hypertension, blindness (retinopathies), amputations, and kidney failure (nephropathies) [4], [7]- [9].…”
Section: Introductionmentioning
confidence: 99%